A new reading of SMEs’ internationalization through entrepreneurial passion: The case of SMEs in Sub‑Saharan Africa - Mahamadou, Zoubeyda (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
Our study aims to take a phenomenological approach to examining the interaction between entrepreneurial passion and the internationalization of Sub-Sahara African SMEs. This will entail the exploration of four concrete cases studies of SMEs from Ivory-Coast, Mali, and Senegal. Given the context of study selected, we also considered the potential impact of the institutional gaps that characterize the markets involved in this relationship. Two important results can be highlighted. First, entrepreneurs who are passionate about developing their country and continent and who are motivated by a social mission are more likely to engage their SME in a dynamic internationalization effort. Secondly, it would appear that the institutional gaps do not prevent the internationalization of SMEs in those instances where directors are passionate about their business developing in that direction.